Posttraumatic growth in Iraqi women who have lost close relatives (Journal Of Educational and Psychological Researches, 2015)
During recent decades, hundreds of thousands of Iraqis lost their lives as a result of wars, economic blockade, or acts of violence and terrorism. The loss of a family member, especially husband makes women suddenly bears full responsibility for the family. Lost could impose new changes in psychological, social, and economical roles. These changes usually combine with the negative effects aftermath the lost trauma. Some of the reports in Iraq showed there were increased and huge numbers of widows and orphans. This study aimed to identify the aspects of Posttraumatic Growth (PTG) in Iraq women who lost their close relatives (especially husbands). 52 of Iraqi women who lost their husband and 49 women who experienced other traumatic events participated in the study. Posttraumatic Growth Inventory was used to collect data. The results showed that women who lost their husband had different levels of growth. There were no significant differences in all growth areas according variables: state of losing (killing or unknown) , number of lost person.